DURING THE REIGN OF THE EMIRATE OF BUKHARA POLITICAL AND ADMINISTRATIVE STRUCTURE - Temurbek B. Bakhramov (Current Research Journal of History, 2022)
This article is about the political and economic situation of the Karshi principality during the Bukhara Emirate and its role in the life of the emirate. Through the article it is possible to know that the oasis is an important trade and economic center in the life of the emirate and has a special place in the period of development. The population of the Karshi principality and its economic centers will be studied in detail.